Natural resource dependence and economic growth in Sulawesi: An empirical study of the resource curse phenomenon - Delfiatiffany, Adhea Mita; Sodik, Jamzani; Nuryadin, Didi (Optimum: Jurnal Ekonomi dan Pembangunan, 2025)
Natural resource abundance does not always guarantee successful regional economic development. In many cases, heavy reliance on extractive sectors can lead to structural disparities and growth stagnation, a condition widely referred to as the resource curse. This study aims to identify early signs of the resource curse in six provinces across Sulawesi Island and to examine the influence of the Regional Resource Curse Index (RRCI) on Gross Domestic Regional Product (GDRP) during the period 2013–2023. A quantitative approach was employed by constructing a composite RRCI derived from the Natural Resource Dependency Index (NRDI) and the Regional Sustainable Development Index (RSDI), followed by regression analysis using Two-Stage Least Squares (2SLS), with nickel commodity prices used as an instrumental variable. The results show that the highest RRCI value was recorded in Southeast Sulawesi at 49.7 in 2023, followed closely by West Sulawesi and North Sulawesi, both with scores of 50.8. While the OLS and Fixed Effects models found no significant effect of RRCI on GDRP, the 2SLS estimation revealed a significant and positive causal relationship, with a lnRRCI coefficient of 0.5438 at the 1% significance level. These findings suggest that regional economic growth remains strongly driven by the extractive sector, although its contribution may be short-lived. This study concludes that Sulawesi Island has not yet fully experienced the resource curse, but early indications are present. Strengthening institutional capacity and developing alternative economic sectors are necessary to prevent long-term dependency on natural resources.